2017
DOI: 10.1016/j.appdev.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Self-determination theory and the role of political interest in adolescents' sociopolitical development

Abstract: In this study we adopted an agentic perspective and used self-determination theory to analyze the role of political interest in youth's sociopolitical development. Inspired by this theoretical framework, we identified indicators of the needs for autonomy, relatedness, and competence within the political sphere. We followed two age cohorts (Swedish 13-and 16-year-olds) over one year, with a total of 1,992 adolescents, who are at a crucial age for sociopolitical development. Results from autoregressive structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…In other words, perhaps the dispositional curiosity measured in this study, in fact, encompassed (or served as a proxy for) adolescents' feelings of political interest. Recall that Russo and Stattin () found that adolescents who are politically interested are more likely to engage with current events and pressing sociopolitical issues in the news. Adolescents more attuned to such current events and sociopolitical issues may also be more committed to engaging in political action that challenges those issues and events they find to be unjust (Russo & Amnå, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, perhaps the dispositional curiosity measured in this study, in fact, encompassed (or served as a proxy for) adolescents' feelings of political interest. Recall that Russo and Stattin () found that adolescents who are politically interested are more likely to engage with current events and pressing sociopolitical issues in the news. Adolescents more attuned to such current events and sociopolitical issues may also be more committed to engaging in political action that challenges those issues and events they find to be unjust (Russo & Amnå, ).…”
Section: Discussionmentioning
confidence: 99%
“…In support of Freire's claims, research on political interest—“a citizen's willingness to pay attention to political phenomena at the possible expense of other topics” (Lupia & Philpot, , p. 1122)—has been connected to political knowledge, political concern, and several other forms of political engagement (Russo & Stattin, ; Verba, Burns, & Schlozman, ). For example, Russo and Stattin () found that political interest was associated with engagement with the news, various forms of discussion and excitement about political talk, and efficacy regarding political skills in adolescents.…”
Section: Curiosity and Sociopolitical Developmentmentioning
confidence: 99%
“…In this manner, three constructs could be incorporated to the present study from SDT: (1) need for autonomy, (2) need for competence, and (3) need for relatedness [ 21 ]. First, autonomy refers to the self-regulation or self-control of behavior [ 44 , 45 ]. Therefore, this dimension recognizes the capacity of encouraging the development of self-inflicted individual actions.…”
Section: Research Framework and Hypothesis Developmentmentioning
confidence: 99%
“…In contrast to forced regulation by external agents, autonomy is related to regulation by the self [45]. It refers to the need to be autonomous [77], and, therefore, it pertains to those personal acts through which individuals control their own behavior. Obviously, this sense impacts directly on the way of behaving due to its capacity to stimulate voluntary acts, even if they come from external initiatives [78].…”
Section: Autonomymentioning
confidence: 99%